Rock Slop Analysis in Duhok Governorate /Bekhair Anticline by Using GIS Technique - Abdulla, Hamed Hassan (Al-Nahrain Journal of Science, 2018)
This study aims to make analysis to the rock slop of Bekhair anticline which lies in the north part of Iraq in the Duhok Governorate by use Digital Elevation Models (DEM) that taken from the Shuttle Radar Topography Mission (SRTM) with GIS technique. The slope image has been created depending on the DEM image and the angle from 35.1 to 81.7 degree given a color to avoid the confuse that may be occur in the image when all angle given a color, the angle from 45.1 to 81.7 concentrate in the middle part of the study area. Also the curvature image has been created. Curvature values represent the morphology of the topography, from the value of this image the more positive value, the higher, the probability of landslide occurrence, also the more positive value occupy the middle part of the study area, so the middle part considered as steep slopes with high value of curvature, thus it is more probable for sliding.